How factors of the therapeutic alliance interact with oxytocin neurotransmission in psychotherapy - Eckert, Marcus; Schandro, Eva (Frontiers in Psychiatry, 2025)
Oxytocin (OT) neurotransmission has emerged as a promising target for alleviating psychiatric symptoms associated with depression, stress, and fear. This mini-review focuses on the therapeutic alliance, highlighting five core components: (1) attachment, (2) empathy, (3) social synchrony, (4) trust and cooperation, and (5) social support. We explore how these factors both influence and are modulated by the oxytocinergic system. Based on current empirical evidence, we propose a conceptual framework in which OT-mediated mechanisms dynamically and reciprocally strengthen the therapeutic alliance. We postulate that activation of the OT system by one or more of these components may synergistically enhance all alliance factors, creating a self-reinforcing cycle with potential therapeutic benefits. Finally, we discuss the clinical implications of this model and identify key avenues for future research.